Requirements of the gas engines considering the use of biogases - Meggyes, Attila; Nagy, Valéria (Periodica Polytechnica Mechanical Engineering, 2009)
In the present publication we are examining the requirements of biogases needed by gas engines. Szolnok University College Technical and Agricultural Faculty as well as Budapest University of Technology and Economics are the two main bases of the research. In the course of our research work, of all the potentially available biogases we chose those ones that seem optimal to operate engines - on the grounds of gas production and methane production. The reasons of our choosing are based on the relatively high energy content, the maximum quantity yield, and the as constant output and quality as possible. In the course of the utilization in the internal combustion engine (in biogas engine) we collected some information on what effects the biogases produced by different kinds of recipes have on the operation of the gas engines, the efficiency and performance with special regards to the emission.